Intranasal Lidocaine for Acute Management of Primary Headaches: A Systematic Review. Issue 10 (7th October 2018) - Dagenais, Renée; Zed, Peter J.
Abstract : Intranasal lidocaine has been studied and recommended as an alternative in the management of acute headache. The objective of this systematic review was to evaluate the efficacy and safety of intranasal lidocaine in the acute management of primary headaches. The MEDLINE (1946 to May 2018), EMBASE (1974 to May 2018), Cochrane Central Register of Controlled Trials (2008 to May 2018), Cumulative Index to Nursing and Allied Health Literature (CINAHL) (1982 to May 2018), and ClincialTrials.gov online databases were searched. Studies conducted in patients with acute primary headache were included if lidocaine was compared with placebo or alternative treatments, lidocaine dosing was specified, and patients' pain before and after treatment were clearly reported. Six studies met the inclusion criteria. Intranasal lidocaine demonstrated potential benefit over placebo in acute pain reduction and need for rescue medication only in the four studies deemed to be of poor quality, not in the two fair‐quality studies. No study reported benefit in preventing headache recurrence or repeat visits to the emergency department. Lidocaine was associated with significantly higher rates of adverse events compared with placebo and may result in lower rates of patient satisfaction. There is insufficient evidence to support the use of intranasal lidocaine in acute management of primary headaches. Further research is warranted to better elucidate whether intranasal lidocaine has a role in the management of specific primary headache subtypes and whether there is an optimal regimen.